Oxygen and the ovarian follicle : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Bioprocess Engineering at Massey University, Palmerston North, New Zealand - Redding, Gabe Peter (Massey University, 2007)
The role oxygen plays in the developing ovarian follicle is of interest not only to the field of developmental biology but also to in-vitro fertilisation (IVF) technologists, as oxygenation of the oocyte is considered to be a potential determinant of oocyte competence. Oxygen transport through the developing ovarian follicle, and practical aspects of the analysis of oxygen in human follicular fluid were investigated in this work. Mathematical modelling of oxygen transport in the pre-antral, and antrallpreovulatory follicle revealed a number of interesting findings, Contrary to previous conclusions (Gosden & Byatt-Smith, 1986), oxygen can reach the oocyte in the small pre-antral follicle. Improved estimates of diffusion coefficients through the granulosa cell layer and the inclusion of fluid voidage in this layer showed that oxygen can also reach the oocyte in large pre-antral follicles. The amount of oxygen that reaches the oocyte in the pre-antral follicle is a function of its size and degree of vascularisation. Symmetrically distributed vascularisation is superior in achieving a well oxygenated follicle. However, the large pre-antral follicle will eventually reach a size beyond which it cannot grow without anoxic regions developing. The size at which this occurs is consistent with the size at which antrum formation is observed in human follicles. The model predicts that the follicle can avoid an anoxic state through antrum formation, and shows that the follicle develops in a way that is consistent with overcoming mass transport limitations. The oxygen status of the follicle during the antrallpre-ovulatory phase of growth requires that the volume of granulosa cells be balanced by the volume of follicular fluid. Further predictions suggest that oocyte respiration becomes sub-maximal at follicular fluid volumes below approximately 4m1, vascularisation levels below 38%, or fluid i dissolved oxygen levels below 5.1 ~01%. These values are consistent with observations in the literature. It was also shown that the measurement of follicular fluid dissolved oxygen levels could provide a simple measure of the respiratory status of the oocyte, and this may be superior to the measurement of follicular vascularisation which requires knowledge of more parameters. Methodology for the analysis of follicular fluid oxygen solubility and diffusivity was developed using a Clark oxygen electrode. Analysis of these parameters showed that they are similar to human plasma, and allowed the predictive uncertainty of the model to be reduced. Experimental studies into the effects of IVF aspiration on follicular fluid were carried out. Aspiration results in significant changes in the properties of follicular fluid. Dissolved oxygen levels rose 5 * 2 vol%, pH increased by 0.04 * 0.01 pH units, and temperature dropped by 7.7 * 1.3 "C. Mathematical modelling of blood contaminated follicular fluid also showed that contamination results in significant changes in the dissolved oxygen of the fluid. This suggests that if the composition of follicular fluid is to be determined (particularly dissolved oxygen), sampling andlor measurement of fluid must take place before the collection vial of the aspiration kit, and blood contamination must be eliminated. Based on this result, the design and testing of devices capable of reliable sampling andlor rneasurement of oxygen levels of follicular fluid was considered. This presents a continuing challenge, including the integration of routine follicular fluid oxygen measurement into clinical practice.
Keywords: Graafian follicle; Oxygen in the body; Oxygen (physiological transport); In-vitro fertilisation (IVF); Ovarian follicles; Fields of Research::320000 Medical and Health Sciences::320600 Medical Physiology